TINDAKAN MEDIK VETERINER MENINGKATKAN PRODUKTIVITAS TERNAK SAPI BALI DI KELOMPOK TANI SATWA LESTARI - Merdana, I. M.; Budiasa, K.; ,, Samsuri; Sudira, I. W.; Sudimartini, L. M. (Buletin Udayana Mengabdi, 2022)
Community service has been carried out in the form of veterinary medical measures aimed at increasing the productivity of Bali cattle at the Satwa Lestari Farmer Group in Musi Village, Gerokgak District, Buleleng Regency. The veterinary medical services provided include counseling on maintenance and health management of Bali cattle, technical guidance on ectoparasitic disease control, administration of deworming medicine, injection of vitamins, induction of lust, and treatment of sick animals. The results of the activity were counseling attended by 21 cattle farmers consisting of administrators and members of livestock farmer groups and also surrounding farmers. The activity continued with technical guidance in mixing drugs to control external parasites such as flies and fleas, implementing sanitation, and cage biosecurity. In the animal health service, 138 cows were successfully performed medical procedures, consisting of 98 broods, 10 males, and 30 calves. The veterinary medical services provided are tailored to the cattle's needs, including vitamin injection, deworming, anti-ectoparasite spraying, injection of an estrus-inducing hormone, and topical antibiotic spraying. We conclude that community service in the form of veterinary medical action is very useful in increasing the knowledge and understanding of farmers in terms of management and reproductive health of cattle, and as concern for their livestock in an effort to increase cattle productivity both in quality and quantity.   Keywords: bali catle, counseling, veterinary medical services